2011
DOI: 10.1210/jc.2011-1682
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Urinary Bisphenol A Levels and Diabetes Mellitus

Abstract: Urinary BPA levels are found to be associated with diabetes mellitus independent of traditional diabetes risk factors. Future prospective studies are needed to confirm or disprove this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
150
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(162 citation statements)
references
References 21 publications
8
150
2
2
Order By: Relevance
“…In the present study, we first demonstrated that long-term oral exposure to BPA induced glucose intolerance after the neonatal period by increasing insulin resistance in a manner that was not related to b cell dysfunction. These findings are consistent with previously published epidemiologic data (Lang et al 2008, Shankar & Teppala 2011, Wang et al 2012 and animal studies (Alonso-Magdalena et al 2006, Wei et al 2011, Batista et al 2012). In two large epidemiologic studies, urinary BPA level was positively associated with type 2 diabetes mellitus (Shankar & Teppala 2011) and with obesity and insulin resistance (Wang et al 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we first demonstrated that long-term oral exposure to BPA induced glucose intolerance after the neonatal period by increasing insulin resistance in a manner that was not related to b cell dysfunction. These findings are consistent with previously published epidemiologic data (Lang et al 2008, Shankar & Teppala 2011, Wang et al 2012 and animal studies (Alonso-Magdalena et al 2006, Wei et al 2011, Batista et al 2012). In two large epidemiologic studies, urinary BPA level was positively associated with type 2 diabetes mellitus (Shankar & Teppala 2011) and with obesity and insulin resistance (Wang et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…However, recent epidemiologic evidence has also implicated BPA in cardiovascular disease, type 2 diabetes, and obesity: increasing serum or urine BPA levels have been positively associated with diabetes mellitus (Lang et al 2008, Shankar & Teppala 2011, cardiovascular disease (Lang et al 2008), obesity, and insulin resistance (Wang et al 2012). Several possible mechanisms have been suggested by animal and in vitro studies, yet whether BPA causes insulin resistance or diabetes is still controversial.…”
mentioning
confidence: 99%
“…There is increasing concern regarding the adverse health effects of BPA on children, given the link between higher levels of urinary BPA and an elevated risk of obesity, type 2 diabetes, and cardiovascular disease based on cross-sectional studies conducted in adults. [1][2][3] Moreover, studies have shown higher urinary concentrations of BPA in children and adolescents compared with adults. 4 Manufacturers have been voluntarily recalling BPA products due to suspicion about the toxic effects on children and other vulnerable populations.…”
mentioning
confidence: 99%
“…37 The range of BPA levels found in humans is from 0.7 to 20 nM. 37,38 To support the evidence that BPA may be a risk for the development of diabetes it is critical to study its effect on human tissues involved in glucose and lipid metabolism, including the endocrine pancreas which is key in glucose homeostasis. The islet of Langerhans is the physiological unit of the endocrine pancreas; it is a group of 1500-3000 cells of five different types and the most abundant are bcells.…”
Section: Bisphenol a As An Endocrine Disruptormentioning
confidence: 99%